Central banks and financial markets : the declining power of US monetary policy - Cömert, Hasan (Cheltenham : Edward Elgar, 2013)
This book shows that the federal reserve has, in the last four decades, gradually lost influence over credit and financial markets. The author shows how dramatic shifts in the financial system undermined the ability of the US federal reserve to control price and the quality of credit.
Includes bibliographical references (pages 186-199) and index.
nmn 24/10/17
Loans
Keywords: Monetary policy; Monetary policy -- History -- 20th century; Banks and banking, Central; Global Financial Crisis, 2008-2009; Devaluation of currency; International economic relations; International finance; United States